Master regulators of epithelial-mesenchymal transition and wnt signaling pathways in juvenile nasopharyngeal angiofibromas - Calanca, Naiade [UNESP]; Binato, Sara Martoreli Silveira; Silva, Sabrina Daniela da; Brentani, Helena Paula; Sennes, Luiz Ubirajara; Pinto, Clóvis Antonio Lopes; Domingues, Maria Aparecida Custódio [UNESP]; Fonseca-Alves, Carlos Eduardo [UNESP]; Rainho, Claudia Aparecida [UNESP]; Rogatto, Silvia Regina (MDPI, 2021)
Juvenile nasopharyngeal angiofibroma (JNA) is a rare fibrovascular benign tumor showing an invasive growth pattern and affecting mainly male adolescents. We investigated the role of epithelial–mesenchymal transition (EMT) and WNT signaling pathways in JNA. Gene expression profiles using nine JNA paired with four inferior nasal turbinate samples were interrogated using a customized 2.3K microarray platform containing genes mainly involved in EMT and WNT/PI3K pathways. The expression of selected genes (BCL2, CAV1, CD74, COL4A2, FZD7, ING1, LAMB1, and RAC2) and proteins (BCL2, CAV1, CD74, FZD7, RAF1, WNT5A, and WNT5B) was investigated by RT-qPCR (28 cases) and immunohistochemistry (40 cases), respectively. Among 104 differentially expressed genes, we found a significantly increased expression of COL4A2 and LAMB1 and a decreased expression of BCL2 and RAC2 by RT-qPCR. The immunohistochemistry analysis revealed a low expression of BCL2 and a negative to moderate expression of FZD7 in most samples, while increased CAV1 and RAF1 expression were detected. Moderate to strong CD74 protein expression was observed in endothelial and inflammatory cells. A significant number of JNAs (78%) presented reduced WNT5A and increased WNT5B expression. Overall, the transcript and protein profile indicated the involvement of EMT and WNT pathways in JNA. These candidates are promising druggable targets for treating JNA.
Keywords: Epithelial–mesenchymal transition; Gene expression profile; Juvenile nasopharyngeal angiofibroma; Tumor microenvironment; Tumor signaling pathways; WNT pathway